Associations of Identity Dimensions with Big Five Personality Domains and Facets. Issue 3 (2nd April 2012) - Klimstra, Theo A.; Luyckx, Koen; Goossens, Luc; Teppers, Eveline; De Fruyt, Filip
Abstract Personality is among the most important factors contributing to individual differences in identity formation. However, previous studies mainly focused on broad personality domains and neglected more specific facets. In addition, it has only recently been recognized that identity formation is guided by multiple types of commitment and exploration. The present study aimed to remedy these limitations by relating the 30 personality facets of the NEO‐PI‐3 to five identity dimensions. In general, identity formation was especially facilitated by high levels of Conscientiousness and, to a lesser extent, also by high levels of Extraversion and low levels of Neuroticism. Openness and Agreeableness predicted greater involvement in both the positive side (i.e. exploration in breadth and depth) and negative side (i.e. ruminative exploration) of the exploration process. Personality facets and their overarching domains, as well as facets underlying the same domain, were often differentially associated with identity dimensions. Additionally, we found that some personality facets both have bright and dark sides, as they predicted both proactive identity work and a weakened sense of identity. Overall, the present study underscores the utility of multidimensional models of identity formation and points to the benefits of considering personality facets in addition to broad domains. Copyright © 2012 John Wiley & Sons, Ltd.